Feed incorporated with the macroalgae Kappaphycus alvarezii for broiler chickens in the starter phase (Revista de Ciências Agroveterinárias, 2020)
An experiment was conducted to evaluate the nutrient digestibility, zootechnical performance, and bone quality parameters of broilers fed a diet containing increasing levels of the macroalgae Kappaphycus alvarezii from one to 21 days of age. A total of 150 Cobb 500® broilers were distributed in a completely randomized design with five treatments, six replications, and five birds per replicate. The total excreta collection method was applied from the 15th and 20th day for the metabolism trial. The following bone quality parameters were assessed: the Seedor index, bone strength, and bone ashes. Dry ground macroalgae were added to the feed in the levels 0%, 0.5%, 1.0%, 1.5% and 2.0%; replacing the inert kaolin. Incorporation of Kappaphycus alvarezii did not influence performance parameters, bone quality parameters, or the coefficients of retention for bone ash and phosphorus. As for feed digestibility, decreases (p
Keywords: algae; amino acids; performance; digestibility; bone quality